2016
DOI: 10.1210/en.2015-1936
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal Di-n-Butyl Phthalate Exposure Alters Sertoli and Leydig Cell Function and Lowers Bone Density in Adult Male Mice

Abstract: Phthalate exposure impairs testis development and function; however, whether phthalates affect nonreproductive functions is not well understood. To investigate this, C57BL/6J mice were fed 1-500 mg di-n-butyl phthalate (DBP) in corn oil, or vehicle only, daily from 4 to 14 days, after which tissues were collected (prepubertal study). Another group was fed 1-500 mg/kg·d DBP from 4 to 21 days and then maintained untreated until 8 weeks for determination of adult consequences of prepubertal exposure. Bones were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Testosterone, the main steroid male sex-hormone, is secreted by Leydig cells of the testes under the control of complex neuroendocrine interactions and is responsible for male sexual activity (El-Kashoury et al 2010 ). The present findings revealed a pronounced decrease in serum testosterone level following exposure of male rats to DBP perhaps due to the activation of estrogen receptors (Alam et al 2010 ), direct adverse effect of the DBP on testicular Leydig cells (Bielanowicz et al 2016 ), inhibition of 3β-HSD and 17β-HSD enzyme, which are essential for steroidogenesis and testosterone biosynthesis (Nelli and Pamanji 2017 ), or due to the induction of oxidative stress (Aly et al 2016 ). Evaluation of the sperm quality indices, including sperm motility, sperm count and sperm viability is valuable indicators of the testicular function and the male reproductive performance (Jenardhanan et al 2016 ).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Testosterone, the main steroid male sex-hormone, is secreted by Leydig cells of the testes under the control of complex neuroendocrine interactions and is responsible for male sexual activity (El-Kashoury et al 2010 ). The present findings revealed a pronounced decrease in serum testosterone level following exposure of male rats to DBP perhaps due to the activation of estrogen receptors (Alam et al 2010 ), direct adverse effect of the DBP on testicular Leydig cells (Bielanowicz et al 2016 ), inhibition of 3β-HSD and 17β-HSD enzyme, which are essential for steroidogenesis and testosterone biosynthesis (Nelli and Pamanji 2017 ), or due to the induction of oxidative stress (Aly et al 2016 ). Evaluation of the sperm quality indices, including sperm motility, sperm count and sperm viability is valuable indicators of the testicular function and the male reproductive performance (Jenardhanan et al 2016 ).…”
Section: Discussionmentioning
confidence: 53%
“…Recently, many studies suspected the involvement of DBP and other phthalates in male reproductive health problems, mainly due to their endocrine-disrupting effects (Zhou et al 2010 ; 2011 ). Several mechanisms have been implicated in the DBP- induced reproductive disorders, including deterioration of sperm quality (Aly et al 2016 ), male reproductive tract deformities (Liu et al 2016 ), Sertoli and Leydig cell dysfunctions (Bielanowicz et al 2016 ), impairment of male fertility, spermatogenesis and steroidogenesis (Nelli and Pamanji 2017 ), and apoptosis of spermatogenic cells (Alam and Hoque 2018 ). Oxidative stress and lipid peroxidation are the main possible mechanisms by which DBP could induce male reproductive disorders as a result of high polyunsaturated fat content in the membrane of sperm ( Zhou et al 2010 , 2011 ; Nelli and Pamanji 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some animal experiments have also confirmed that DBP is toxic to brain, lungs, liver, testes, and kidneys 11–14 . In addition, Bielanowicz et al reported that DBP exposure can reduce femoral length, bone mineral content, and bone mineral density in mice 15 . Pu et al reported that DBP exposure can lead to down‐regulation of bone growth‐related gene expression, achondroplasia disorder, and spinal curvature in zebrafish 16 .…”
Section: Introductionmentioning
confidence: 97%
“…[11][12][13][14] In addition, Bielanowicz et al reported that DBP exposure can reduce femoral length, bone mineral content, and bone mineral density in mice. 15 Pu et al reported that DBP exposure can lead to down-regulation of bone growth-related gene expression, achondroplasia disorder, and spinal curvature in zebrafish. 16 However, the specific mechanism of skeletal dysplasia caused by DBP has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent animal studies provide experimental evidence of a link between phthalate exposure and inhibitory effects on healthy bone processes and homeostasis in rodents. Two experimental studies found that adult male mice exposed to low dibutyl phthalate (DBP) doses prepubertally [ 10 ] and to di(2-ethylhexyl) phthalate (DEHP) in adulthood [ 11 ] had lower BMD and altered bone microstructure. Additional studies determined that BMD was significantly reduced in ovariectomized mice treated with high doses of DEHP [ 12 ] and in intact mice injected with diisononyl phthalate (DINP) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%